The Effect of Debt to Equity Ratio and Return on Equity on the Stock Price of PT Astra Agro Lestari from 2013 to 2023 - Yanita, Poni; Surya , Tiara Lilis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The purpose of this study is to analyze the effect of debt-to-equity ratio (DER) and Return on equity (ROE) on the stock price of PT Astra Agro Lestari Tbk for the period 2013 to 2023. The method used in this study is multiple linear regression analysis with stock price as the dependent variable and DER and ROE as independent variables. In contrast, DER is proven to have no significant effect on stock prices with a p-value above 0.05, indicating that investors may not consider DER as a major factor in determining stock prices. While this study provides important insights for management and investors regarding the importance of Return on equity (ROE) performance in determining market value, it also provides insights into the broader context of DER.